2006
DOI: 10.1128/mcb.26.10.3835-3841.2006
|View full text |Cite
|
Sign up to set email alerts
|

Dph3, a Small Protein Required for Diphthamide Biosynthesis, Is Essential in Mouse Development

Abstract: The translation elongation factor 2 in eukaryotes (eEF-2) contains a unique posttranslationally modified histidine residue, termed diphthamide, which serves as the only target for diphtheria toxin and Pseudomonas aeruginosa exotoxin A. Diphthamide biosynthesis is carried out by five highly conserved proteins, Dph1 to Dph5, and an as-yet-unidentified amidating enzyme. The evolutionary conservation of the complex diphthamide biosynthesis pathway throughout eukaryotes implies a key role for diphthamide in normal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 20 publications
2
68
0
Order By: Relevance
“…In support of this notion, evidence from research groups including our own has shown that diphthamide defects increase translational frame-shifting (Ortiz et al, 2006;Bär et al, 2008). Moreover, homologues of diphthamide synthesis genes (DPH1/OVCA1 and DPH3/KTI11) affect the proliferation and development of mammalian cells, which is why inactivation of DPH3/KTI11 is associated with tRNA modification defects and neurodegeneration and mutations in DPH1/OVCA1 revealed a tumour suppressor role for this diphthamide synthesis gene in ovarian cancer (Chen & Behringer, 2004;Nobukuni et al, 2005;Huang et al, 2005;Liu et al, 2006;Kim et al, 2010 Whether or not this implies structural or regulatory roles for diphthamide in mRNA translation remains to be seen. The latter, however, is intriguing with the emergence of a cellular ADP-ribosyltransferase that resembles the diphthamide-dependent ADPribosylation reaction by DT (Lee & Iglewski, 1984;Jäger et al, 2011).…”
Section: Biological Significance For Diphthamide Modification Of Ef2mentioning
confidence: 75%
See 1 more Smart Citation
“…In support of this notion, evidence from research groups including our own has shown that diphthamide defects increase translational frame-shifting (Ortiz et al, 2006;Bär et al, 2008). Moreover, homologues of diphthamide synthesis genes (DPH1/OVCA1 and DPH3/KTI11) affect the proliferation and development of mammalian cells, which is why inactivation of DPH3/KTI11 is associated with tRNA modification defects and neurodegeneration and mutations in DPH1/OVCA1 revealed a tumour suppressor role for this diphthamide synthesis gene in ovarian cancer (Chen & Behringer, 2004;Nobukuni et al, 2005;Huang et al, 2005;Liu et al, 2006;Kim et al, 2010 Whether or not this implies structural or regulatory roles for diphthamide in mRNA translation remains to be seen. The latter, however, is intriguing with the emergence of a cellular ADP-ribosyltransferase that resembles the diphthamide-dependent ADPribosylation reaction by DT (Lee & Iglewski, 1984;Jäger et al, 2011).…”
Section: Biological Significance For Diphthamide Modification Of Ef2mentioning
confidence: 75%
“…In the budding yeast Saccharomyces cerevisiae, diphthamide biosynthesis requires at least five genes, DPH1-DPH5 (Liu et al, 2004), two mammalian homologues of which (DPH1/OVCA1 & DPH3/KTI11) are intriguingly involved in embryonic development and cell proliferation in rodents and humans (Fichtner & Schaffrath, 2002;Chen & Behringer, 2004;Fichtner et al, 2003;Liu & Leppla, 2003;Nobukuni et al, 2005;Liu et al, 2006). Though complex in nature, the diphthamide pathway has been shown to be molecularly dissectable.…”
Section: Posttranslational Biosynthesis Of Diphthamide On Ef2mentioning
confidence: 99%
“…OVCA1 −/− and Dph4 −/− mice phenocopied each other with a delay in embryo development starting as early as E8.5, and having 100% prenatal lethality (20)(21)(22) (Table S2). Interestingly, the eEF2 G717R/G717R mice displayed a milder phenotype, with a small fraction surviving to adulthood.…”
Section: Resultsmentioning
confidence: 99%
“…Diphthamide deficiency can be induced by deletion of the genes involved in the diphthamide biosynthesis (20)(21)(22). However, these genes may have pleiotropic functions, as seen with Dph3 involvement in tRNA anticodon modifications (23).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation